A pilot study for treatment of severe COVID-19 pneumonia by aerosolized formulation of convalescent human immune plasma exosomes (ChipEXO™) - Gül, Fethi; Gonen, Zeynep Burcin; Jones, Olcay Y.; Taşlı, Neslihan Pakize; Zararsız, Gökmen; Ünal, Ekrem; Özdarendeli, Aykut; Şahin, Fikrettin; Eken, Ahmet; Yılmaz, Semih; Karakukçu, Musa; Kırbaş, Oğuz Kaan; et al. (Frontiers in Immunology, 2022)
This is a single-center prospective, open-label, single arm interventional study to test the safety and efficacy of recently described ChipEXO™ for severe COVID-19 pneumonia. The ChipEXO™ is a natural product derived from convalescent human immune plasma of patients recovered from moderate COVID-19 infection. In September 2021, 13 patients with pending respiratory failure were treated with ChipEXO™ adapted for aerosolized formulation delivered via jet nebulizer. Patients received 1-5x1010 nano vesicle/5 mL in distilled water twice daily for five days as an add-on to ongoing conventional COVID-19 treatment. The primary endpoint was patient safety and survival over a 28-day follow-up. The secondary endpoint was longitudinal assessment of clinical parameters following ChipEXO™ to evaluate treatment response and gain insights into the pharmacodynamics. ChipEXO™ was tolerated well without any allergic reaction or acute toxicity. The survival rate was 84.6% and 11 out of 13 recovered without any sequel to lungs or other organs. ChipEXO™ treatment was effective immediately as shown in arterial blood gas analyses before and two hours after exosome inhalation. During the 5 days of treatment, there was a sustainable and gradual improvement on oxygenation parameters: i.e. respiratory rate (RR) [20.8% (P < 0.05)], oxygen saturation (SpO2) [6,7% (P < 0.05)] and partial pressure of oxygen to the fraction of inspired oxygen (PaO2/FiO2) [127.9% (P < 0.05)] that correlated with steep decrease in the disease activity scores and inflammatory markers, i.e. the sequential organ failure assessment (SOFA) score (75%, p < 0.05), C-reactive protein (46% p < 0.05), ferritin (58% p = 0.53), D-dimer (28% p=0.46). In conclusion, aerosolized ChipEXO™ showed promising safety and efficacy for life-threatening COVID-19 pneumonia. Further studies on larger patient populations are required to confirm our findings and understand the pathophysiology of improvement toward a new therapeutic agent for the treatment of severe COVID-19 pneumonia.